Réponses

  • Utilisateur Brainly
2013-12-01T13:26:11+01:00
A = ( 2x  - 5) (3 - x)
   =6x-15-2x²+5x
   =-2x²+11x-15

B = (3x - 4)²
   =9x²-24x+16

C = (4x + 9) (4x - 9)
   =16x²-81

D = (9 + 5x)²
   =25x²+90x+81

E = (5x - 2)² + (x - 7) (5x + 2)

   =25x²-20x+4+5x²+2x-35x-14
   =30x²-53x-10
2013-12-01T13:29:39+01:00
A = (2x -5)(3-x)
A = 6x-2x²-15+5x
A = -2x²+11x-15

B = (3x-4)²
B = 9x²-24x+16

C = (4x+9)(4x-9)
C = 16x²-36x+36x-81
C = 16x²-81

D = (9+5x)²
D = 81+90x+25x²
D = 25x²+90x+81

E = (5x-2)²+(x-7)(5x+2)
E = 25x²-20x+4+5x²+2x-35x-14
E = 30x²-53x-10